PENDIDIKAN ISLAM DAN KESETARAAN GENDER - Mujib, Siti Marhamah (IAIN Pekalongan, 2010)
Abstract: Science can only get someone through a process called education. In other words, to get the science, every servant of God must take the education process. studying obligation is an obligation that applies to both Muslim men and Muslim women, meaning they have the same rights to study in this context is to obtain education. The right to obtain knowledge is a fundamental right directly guaranteed by Allah and His Messenger. Lots of history of hadith which records the process of discussion of women at the time of the Prophet, including the process of their struggle for equal education rights with men.